1965
DOI: 10.2307/3895497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One Year's Nitrogen Fertilization on Native Vegetation under Clipping and Burning

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…Old-field succession sometimes begins on nutrient poor soils that are low in organic matter (Odum 1960;Gay & Dwyer 1965;Golley 1965;Monk & Gabrielson 1985;Inouye et al 1987;Tilman 1987). For example, N contents of forest and prairie soils are often twice those of recently abandoned agricultural fields in east-central Minnesota (Inouye et al 1987;Pastor et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Old-field succession sometimes begins on nutrient poor soils that are low in organic matter (Odum 1960;Gay & Dwyer 1965;Golley 1965;Monk & Gabrielson 1985;Inouye et al 1987;Tilman 1987). For example, N contents of forest and prairie soils are often twice those of recently abandoned agricultural fields in east-central Minnesota (Inouye et al 1987;Pastor et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous investigations have been concerned with fertilizing species that are important on the tallgrass prairie, such as little bluestem, Schizachyrium scoparium (White 1961, Dickinson 1964, Nixon and McMillan 1964, Reardon and Huss 1965, van Amburg and Dodd 1970, Rao et al 1973, Senter 1975, Waller et al 1975. In other instances, fertilizers have been added to the prairie and responses have been measured in terms of yield (Gay and Dwyer 1965, McMurphy 1970, Owensby et al 1970, Hyde and Owensby 1973, Dodd and Lauenroth 1979, species com-positional changes (Huffine and Elder 1960, Owensby eta!. 1970, Hamer and Harper 1973, and forage quality (Dickinson 1964, Owensby et al 1970, Woolfolk et al 1973, Senter 1975, Launchbaugh and Owensby 1978:38-40, Samuel et al 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Dwyer (1969) in a greenhouse study reported that clipping at either the 3 or 5 cm level aboveground each 10 days for 102 days was too severe for maximum growth of blue grama (Bouteloua gracilis). However, in an earlier study Gay and Dwyer (1965) found that nitrogen fertilized tall grass prairie in excellent range condition clipped once at ground level during the growing season produced more dry matter than that not clipped and fertilized. McGinnies (1973) found that seedlings of crested wheatgrass from spring plantings clipped to a 1.3 cm stubble reduced survival by 13% but clipping to ground level reduced survival by 61%.…”
mentioning
confidence: 85%